Strengthening Consumer Buying Interest Through Service Quality and Product Existence and Price - Nurhayati, N.; Lewangka , Oesman; Badawi, Andi Mappatompo (Manunggal Halim Jaya, 2024)
MSME actors such as the Roti Bakar 19 Bandung are one of the economic institutions that contribute positively to economic growth so they need to be empowered as an integral part of the people's economy which has a strategic position, role and potential to create a national economic structure that is more balanced, developed and just (Amien & Zulkarnaen, 2022) . The aim of this research is to analyze and test the influence of price and product on perceptions of service quality at the Roti Bakar 19 Bandung in Makassar City. To analyze and test the influence of price, product, perceived service quality on consumer buying interest at the Roti Bakar 19 Bandung in Makassar City. To analyze and test the effect of price and product on consumer buying interest through perceptions of service quality at the Roti Bakar 19 Bandung in Makassar City. This type of research uses quantitative methods. This research was conducted at the Roti Bakar Bandung 19 Makassar City. Sampling used Malhotra theory by calculating 85 samples. The data collection method used in this research was by using questionnaires and interviews. Researchers used a Likert scale as a measurement scale for the questionnaire. The analysis technique used is path analysis. The results of this study indicate that the product has an insignificant positive influence on quality of service with. Price has a significant negative influence on consumer buying interest. The product has a significant positive influence on interested in buying. Service quality has a significant influence on buying interest. Price has a significant influence on consumer buying interest through service quality. The product has a positive and significant influence on Consumer buying interest through service quality.